2022
DOI: 10.1177/14757257221136660
|View full text |Cite
|
Sign up to set email alerts
|

The Testing Effect in the Lecture Hall: Does it Depend on Learner Prerequisites?

Abstract: The benefits of practice testing for long-term learning are well established in many contexts. However, little is known about learner characteristics that might moderate its effectiveness. The effects of practice tests might depend on individual prerequisites for learning, especially in real-world educational settings. We explored whether the effects of practice testing in a regular university lecture would depend on cognitive (e.g., prior knowledge), motivational (e.g., learning motivation), or emotional (tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…One question of particular interest is how the testing effect may be modulated by prior knowledge of the tested domain. Several studies have examined whether the degree of learners’ prior knowledge correlates with the magnitude of the testing effect, with mixed results: One study found that retrieval practice has a compensatory effect such that it is more beneficial for learners with low existing topic knowledge (Cogliano et al, 2019 , EL: 5), another conversely found that retrieval practice is more beneficial for learners with high knowledge (Carpenter et al, 2016 , EL: 5), and others found testing equally effective regardless of prior topic knowledge (Glaser & Richter, 2022 , EL: 5; Xiaofeng et al, 2016 , EL: 5), although all of these studies are limited by their correlational nature. More recently, in an experimental study, Buchin and Mulligan ( 2023 , EL: 4) manipulated learners’ topic knowledge by having them study an academic topic across multiple days of training before introducing a retrieval-practice manipulation; this study found that the testing effect equally benefited high-knowledge and low-knowledge learners.…”
Section: Moderatorsmentioning
confidence: 99%
“…One question of particular interest is how the testing effect may be modulated by prior knowledge of the tested domain. Several studies have examined whether the degree of learners’ prior knowledge correlates with the magnitude of the testing effect, with mixed results: One study found that retrieval practice has a compensatory effect such that it is more beneficial for learners with low existing topic knowledge (Cogliano et al, 2019 , EL: 5), another conversely found that retrieval practice is more beneficial for learners with high knowledge (Carpenter et al, 2016 , EL: 5), and others found testing equally effective regardless of prior topic knowledge (Glaser & Richter, 2022 , EL: 5; Xiaofeng et al, 2016 , EL: 5), although all of these studies are limited by their correlational nature. More recently, in an experimental study, Buchin and Mulligan ( 2023 , EL: 4) manipulated learners’ topic knowledge by having them study an academic topic across multiple days of training before introducing a retrieval-practice manipulation; this study found that the testing effect equally benefited high-knowledge and low-knowledge learners.…”
Section: Moderatorsmentioning
confidence: 99%